Osobowość nauczycieli a ich praca z dziećmi migrantami w szkole podstawowej - Pamuła-Behrens, Małgorzata; Hennel-Brzozowska, Agnieszka (Studia Edukacyjne, 2020)
Research on the personality of primary school teachers and on their level of competence in teaching migrant children, including their own migration experience and their attitudes toward training for better education of foreign pupils, was conducted in 2016, using Big Five NEO-FFI and a questionnaire constructed by the authors (PPNUC). The subjects work in a big Polish city and their school is attended by Ukrainian and Vietnamese migrant children; half of the teachers (called NU) have the migrant children in their classes, the other half do not (NN). The results have shown, among others, that NU teachers have higher extraversion scores than NN and that younger teachers have a more positive attitude toward training programs for educating migrant children.